Mind the Microgap in Iridescent Cellulose Nanocrystal Films - Fernandes, Susete N. (2021)
This work was funded by FEDER funds through the COMPETE 2020 Program and National Funds through FCT - Portuguese Foundation for Science and Technology under the Projects No, PTDC/FIS-NAN/0117/2014, and PTDC/CTM-BIO/6178/2014. S.N.F. acknowledges the Minister of Science, Technology and Higher Education for National Funds, European Social Funds and FCT for fellowship number SFRH/BDP/78430/2011. The authors also acknowledge FAPESP, CNPq, INCT-FCx from Brazil.